Do Household Characteristics Influence Private Car and Motorcycle Ownership? Evidence from a Case Study in Yogyakarta Urban Area, Indonesia - Rachmi, Dewi Prathita; Irawan, Muhammad Zudhy; Dewanti, Dewanti (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2022)
Yogyakarta is listed among the cities with the worst congestion in Indonesia. Besides, the development of Yogyakarta has now expanded to the surrounding area and agglomerated into the Yogyakarta Urban Area (KPY). Private vehicle ownership is closely correlated to the characteristics of households. This study aims to analyze the correlation of the level of private vehicle ownership with the characteristics of households and the correlation of private vehicle ownership towards the responses of households with transportation policies that will be implemented in the future. This study fully used secondary data. The total respondents were 8,810 households, and the research location was the Yogyakarta Urban Area (KPY). The path analysis was employed to find out the causal relation between variables and the contribution between variables in the analysis. The variables used were gender, age, education level of the heads of households, total household income, the number of adult family members (> 17 years old), the number of children (<17 years old), the number of working family members, total motorcycle licenses in a household, total driver's licenses in a household, total motorcycle ownership in a household, total car ownership in a household, and the responses of households to the transportation policies that will be applied. The results of the study show that motorcycle ownership in a household is influenced by gender, age, the level of education of the heads of households, total household income, the number of adult family members, the number of children, the number of working family members, and total motorcycle licenses in a household. Meanwhile, car ownership in a household is influenced by age, total household income, the number of working family members, and total driver's licenses in a household. There is also a correlation between motorcycle and car ownership. Increasing car ownership in a household has a positive correlation with motorcycle ownership. Furthermore, motorcycle ownership has a good significance value and a positive correlation with pedestrianization policies prioritizing public transportation in the Mangkubumi-Malioboro-Kraton area.